Enhance Business Settings and Transactions in the Digital Age - Henry Aspan; Fitria Ramadhani Siregar; Indawati Lestari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
In the current era of globalization, the ease and speed of obtaining something is highly sought after, including the ease and speed of obtaining financial services. This new method is a digital financial service that offers and provides convenience and speed of financial services. It is hoped that this method will provide convenience for the public to obtain financial services. But we need to remember that in our constitution, Indonesia is a state of law so that everything that is done in this country must be based on the law. Including digital finance businesses must be regulated and supervised by existing laws in Indonesia. Based on the research results, it is known that the financial business in Indonesia is regulated and supervised by three institutions, namely the Ministry of Communication and Information, Bank Indonesia, and the Financial Services Authority.